Kenya, into the second decade : report of a mission sent to Kenya by the World Bank - World Bank.; Burrows, John R. (Baltimore : Published for the World Bank by the Johns Hopkins University Press, 1975)
Kenya at the time of publishing this volume was in the second year of its second decade as an independent nation. Behind it lies a record of sustained growth in production and income that has rarely been surpassed by countries in Kenya's stage of development. Yet by the end of the first decade, Kenya confronted a set of problems that has become all too familiar in the developing world: rapid population growth and slow growth of rural incomes, leading to continuing migration from rural to urban areas, rising urban unemployment, and increasing poverty unmitigated by the benefits of growth. In a changing world environment, these and other obstacles present Kenya's leaders with an even greater challenge through the second decade and beyond. This book suggests a strategy which the authors consider most likely to alleviate poverty and reduce unemployment, while maintaining growth and improving the distribution of its benefits - a strategy which the government of Kenya is attempting to pursue. It aims at progressive change in the structure of growth, with greater emphasis on agriculture and industries based on domestic resources. It also calls for reform in the process of growth, especially through changes in factor prices to induce more efficient use of scarce resources, particularly of capital and skilled manpower, and the generation of greater benefits, chiefly in terms of employment and income.
Includes bibliographical index
mf25/01/2019
Loan
Keywords: Economic conditions; Kenya